THE INFLUENCE OF TRUST, RISK AND MOTIVATION ON THE INTENTION TO USE THE SHOPEE BLESSING APPLICATION WITH EXPERIENCE AS A MODERATION VARIABLE - Nurul Wahida Hidayat; Slamet Haryono (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2021)
The purpose of this study is to find out whether trust affects the intention to use the shopee blessing application, whether risk affects the intention to use the shopee blessing application, and whether motivation affects the intention to use the shopee blessing application. Then the researcher added experience as a moderation variable in the study that can moderate trust, risk, and motivation towards the intention of using the shopee blessing application. This study uses the UTAUT2 theory which explains the extent of the difference between the intention to use and the actual use of technology by consumers. To obtain research data, researchers shared a questionnaire by selecting a Likert scale as a measurement, using the STATA version 16 application as data analysis. To see the results of the study, researchers used moderated regression analysis (MRA). From the results of the research conducted by the researcher, it can be concluded, that the trust variable affects the intention to use and the experience can moderate the trust in the intention to use the shopee blessing application, the risk variable does not affect the intention to use nor can the experience moderate the risk to the intention to use the blessing shoppe application, and the motivation variable does not affect the intention to use the blessing shoppe application, and the motivation variable does not affect the intention to use but experience can moderate motivation towards the intention of using the blessings.